Design Smart Attendance laverging People Identification System as Service Using SoaML for Smart Campus - Iwan Setiawan (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2017)
One feature of smart campus is the identification of people[1]. This feature serves to record civitas data and guests who enter the campus for the purpose to monitor the university. This feature is very important and needs further research to be developed. In this research will be designed people system that can be used for various purposes by all sectors in the university who need this system. This will become clearer in this study.